The initial mass function in the extended ultraviolet disc of M83. Issue 2 (22nd November 2019) - Bruzzese, S M; Thilker, David A; Meurer, G R; Bianchi, Luciana; Watts, A B; Ferguson, A M N; Gil de Paz, A; Madore, B; Martin, D Christopher; Rich, R Michael
ABSTRACT: Using Hubble Space Telescope ACS/WFC data we present the photometry and spatial distribution of resolved stellar populations of four fields within the extended ultraviolet disc (XUV disc) of M83. These observations show a clumpy distribution of main-sequence stars and a mostly smooth distribution of red giant branch stars. We constrain the upper end of the initial mass function (IMF) in the outer disc using the detected population of main-sequence stars and an assumed constant star formation rate (SFR) over the last 300 Myr. By comparing the observed main-sequence luminosity function to simulations, we determine the best-fitting IMF to have a power-law slope α = −2.35 ± 0.3 and an upper mass limit $M_{\rm u}=25_{-3}^{+17} \, M_\odot$ . This IMF is consistent with the observed H $\rm α$ emission, which we use to provide additional constraints on the IMF. We explore the influence of deviations from the constant SFR assumption, finding that our IMF conclusions are robust against all but strong recent variations in SFR, but these are excluded by causality arguments. These results, along with our similar studies of other nearby galaxies, indicate that some XUV discs are deficient in high-mass stars compared to a Kroupa IMF. There are over one hundred galaxies within 5 Mpc, many already observed with HST, thus allowing a more comprehensive investigation of the IMF, and how it varies, using the techniques developed here.